The beneficial effect of propolis on cerulein-induced experimental acute pancreatitis in rats - Mehmet BÜYÜKBERBER; M. Cemil SAVAŞ; Cahit BAĞCI; Mehmet KORUK; M. Taner GÜLŞEN; Ediz TUTAR; Tuğba BİLGİÇ and Rukiye DEVECİ and Can KÜÇÜK (Turkish Journal of Gastroenterology, 2019)
-